2005
DOI: 10.1194/jlr.m500151-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Free fatty acid release from human breast cancer tissue inhibits cytotoxic T-lymphocyte-mediated killing

Abstract: Immune-mediated antitumor activities confront a variety of tumor-mediated defense mechanisms. Here, we describe a new mechanism involving FFA that may allow breast cancer to evade immune clearance. We determined the IC 50 at which unbound free fatty acids (FFA u ) inhibit murine cytotoxic T-lymphocyte (CTL)-mediated killing to assess the physiologic relevance of this phenomenon. We found that the IC 50 for unbound oleate is 125 ؎ 30 nM, ‫ف‬ 200-fold greater than normal plasma levels. FFA inhibition, however, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 41 publications
3
56
0
1
Order By: Relevance
“…Linoleic acid does not only induce PAI-1 (a prognostic marker for breast cancer) secretion through SMAD4 (similar to mothers against decapentaplegic-4) but also enhances the migratory potential of the highly invasive MDA-MA-468 breast cancer cell line 46 . FFA secreted by primary breast cancer into the interstitial fluid were found to inhibit the cytolytic activity of the infiltrating cytotoxic T lymphocytes (CTLs), 47 providing yet another example of tumor lipid metabolism effecting the tumor micro- and possibly also macroenvironment. A large multicenter study revealed a positive association between serum palmitic acid with a high relative risk of 1.90 for prostate cancer and an inverse association with stearic acid, respectively 48 .…”
Section: Metabolism Of the Tumor Macroenvironmentmentioning
confidence: 99%
“…Linoleic acid does not only induce PAI-1 (a prognostic marker for breast cancer) secretion through SMAD4 (similar to mothers against decapentaplegic-4) but also enhances the migratory potential of the highly invasive MDA-MA-468 breast cancer cell line 46 . FFA secreted by primary breast cancer into the interstitial fluid were found to inhibit the cytolytic activity of the infiltrating cytotoxic T lymphocytes (CTLs), 47 providing yet another example of tumor lipid metabolism effecting the tumor micro- and possibly also macroenvironment. A large multicenter study revealed a positive association between serum palmitic acid with a high relative risk of 1.90 for prostate cancer and an inverse association with stearic acid, respectively 48 .…”
Section: Metabolism Of the Tumor Macroenvironmentmentioning
confidence: 99%
“…As no normal (straight chain FA) controls were run, the effect may be due to high free fatty acid concentrations taken up by cells as intact lipid laden microparticles and may not be completely specific to the tested BCFA, isopentadecanoic acid (13-methyl tetradecanoic acid, 13-MTD). Indeed, unbound FA mediated cellular signaling events are reversed by the addition of albumin [20, 21]. BSA has seven binding sites with high to moderate affinity for fatty acids, 2–3 of which are high affinity with equilibrium constants on the order of 10 8 M −1 for palmitate [22].…”
Section: Discussionmentioning
confidence: 99%
“…1 and No. 5 interferes with a variety of cellular functions including immune and cardiac functions [19,20]. Limiting Intralipid may therefore reduce acute bilirubin encephalopathy as well as FFA u -mediated toxicity.…”
Section: Discussionmentioning
confidence: 99%